2001
DOI: 10.1038/83713
|View full text |Cite
|
Sign up to set email alerts
|

The immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome (IPEX) is caused by mutations of FOXP3

Abstract: IPEX is a fatal disorder characterized by immune dysregulation, polyendocrinopathy, enteropathy and X-linked inheritance (MIM 304930). We present genetic evidence that different mutations of the human gene FOXP3, the ortholog of the gene mutated in scurfy mice (Foxp3), causes IPEX syndrome. Recent linkage analysis studies mapped the gene mutated in IPEX to an interval of 17-20-cM at Xp11. 23-Xq13.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
2,018
4
39

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,966 publications
(2,080 citation statements)
references
References 12 publications
19
2,018
4
39
Order By: Relevance
“…These studies strongly indicate that a threshold of Treg function is required throughout life to restrain autoreactive T cells and/or inflammatory responses, and this prevents autoimmune disease onset. The early development of autoimmune disease in IPEX patients, who lack FOXP3 and Treg,23 confirms that Treg are also essential in humans 24. Functional defects in Treg in type 1 diabetes and inflammatory bowel disease have been reported,25, 26 but there are conflicting reports in the literature about reduced Treg numbers in autoimmune cohorts.…”
Section: Treg and Diseasementioning
confidence: 89%
See 1 more Smart Citation
“…These studies strongly indicate that a threshold of Treg function is required throughout life to restrain autoreactive T cells and/or inflammatory responses, and this prevents autoimmune disease onset. The early development of autoimmune disease in IPEX patients, who lack FOXP3 and Treg,23 confirms that Treg are also essential in humans 24. Functional defects in Treg in type 1 diabetes and inflammatory bowel disease have been reported,25, 26 but there are conflicting reports in the literature about reduced Treg numbers in autoimmune cohorts.…”
Section: Treg and Diseasementioning
confidence: 89%
“…Since its identification as the key transcription factor for the formation and function of Treg in mouse and humans,23, 31, 32 FOXP3 has been the subject of much investigation. Molecular mechanisms for the action of FOXP3 in shaping regulatory T cells and their critical role in maintaining lifelong tolerance are now being better understood.…”
Section: Transcriptional Control Of Treg Formation and Functionmentioning
confidence: 99%
“…Several studies have indicated that genetic defects in FOXP3 may lead to its altered levels and functionality and, indeed, autoimmune disorders have been related to various deleterious mutations in FOXP3 [34][35][36][37][38]. With respect to vitiligo, polymorphisms of FOXP3 have been associated with predispostion to the development of the disease (Table 2) [39-41].…”
Section: Forkhead Box P3mentioning
confidence: 99%
“…Indeed, infection of naive T cells with a retroviral vector expressing FoxP3 was sufficient to induce a regulatory phenotype in these cells 3 . Moreover, deletion or loss of function of the FoxP3 encoding gene determines an autoimmune phenotype both in humans (the immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome) 4 and mice (Scurfy) 5 . Functionally Tregs have been studied both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%